(untitled) (Progressive Agriculture, 2013)
Rural women are silent workers and major contributors to rural economy. Their economic contributions are often appreciated but not widely recognized. The purpose of the study was to make the participation of rural women in farm and non-farm activities visible and their contribution in generating household income. Data were collected from a purposively-drawn sample of 60 rural households consisting of 20 low, 20 medium and 20 high income households. The obtained data were analyzed by using tabular and statistical techniques. Women of these three categories contributed to Tk. 19398, 24180 and 20917.50 which were 35.18, 25.11 and 14.20 per cent of total household income respectively. It was evident that, female participation of low and medium income households is markedly higher in non-farm activities than the high income households. The results of the study showed clear evidences of greater extent of womens participation in farm and non-farm activities as well as in various household decision making events. The findings of the study suggest that, in order to enhance women participation in farm and non-farm activities and their contribution to household income, the quality and status of support service like input supply, credit facilities, extension and motivation, need-based training should be improved. A successful government and non-government collaborative programme can best address these issues in an integrated manner. DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16878 Progress. Agric. 20(1 & 2): 245 251, 2009